Active flutter control of a bridge-flap system considering aerodynamic interferences in practical considerations. (1st June 2022) - Li, Ke; Zhao, Lin; Hui, Yi; Yang, Qingshan; Chen, Zengshun; Qian, Guowei
Abstract: Designing bridges with spans larger than 2000 m is challenging. One critical problem is that the flutter stability of such bridges is extremely weak. In past studies, actively controlled flaps were found to improve the flutter stability performance. However, in those studies, the deck was always assumed to be an ideal streamlined plate to simplify the aerodynamic interference effect in the deck-flap system. This simplification limits the application of this technique on real projects. To improve the applicability, we adopt a typical bluff body deck to investigate the effect of the active flaps under different wind attack angles. The novelty of this work is the analysis of the aerodynamic interference and resulting control impact considering the application scenario. The tests are conducted through the computational fluid dynamic method. To give intuitive explanations of the aerodynamic interference, the distributed aerodynamic characteristics method is innovatively introduced to quantify the contribution of flap on the flutter stability during the control process. Our results show that the leading flap has a dominant contribution to the flutter stability by inducing the beneficial aerodynamic damping on the deck's leading surfaces. Its optimal phase should be about π /2 lagging from the deck's torsional motion. In comparison, the effect of the trailing flap is unstable under different wind attack angles. To guarantee a robust control effect, it is suggested that it remains stationary.